Pengaruh Ketahanan Pangan Terhadap Stabilitas Ekonomi Kabupaten Pandeglang Pada Tahun 2019-2022 - Andini, Wulan; Salsabila, Misfah; Yulianti, Oliviani; Arsitamira, Melinda Nur; Pradua, Raihan Septa; Dermawan, Deris (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2024)
This study analyzes the impact of food security on economic stability in Pandeglang Regency during the period of 2019-2022. Food security, which encompasses availability, accessibility, and quality of food, is a fundamental element in supporting community welfare and economic stability. As an agrarian region, Pandeglang faces significant challenges such as production fluctuations due to climate change and supply chain disruptions during the COVID-19 pandemic. The research findings indicate that food security positively contributes to price stability and purchasing power of the community. However, there are obstacles such as limited infrastructure and access to agricultural technology that need to be addressed. This study recommends policies to enhance food diversification and strengthen the agricultural sector to bolster local food security.